Progress in initial French composition: A case study at the University of Costa Rica - Cambronero-Artavia, María del Pilar (2026)
This article presents the findings of an action-research project conducted in a composition course Expresión Escrita I at the University of Costa Rica. This study aimed to analyze the progress in the quality of paragraph composition among students of French as a Foreign Language. The research stems from the premise that writing deficiencies are often linked to structural gaps in the student’s first language (Spanish). Using a quantitative approach, the study was carried out with 15 students and structured into 3 stages: an initial diagnostic in Spanish, a technical instruction phase, and a final evaluation in French. The results reveal a significant improvement in sentence structure. Notably, 40% of the participants achieved a higher linguistic proficiency in French production than in their native language through systematic instruction, compensating also for L1 weaknesses.